Reading Strategies Used By English Education Students At Universitas Negeri Padang - Oktaria, Rinda; Syafei, An Fauzia Rozani (Universitas Negeri Padang, 2025)
This study aimed to identify the types of reading strategies used and the most frequently used of reading strategies among 2022 students of English Education at Universitas Negeri Padang. This study is descriptive method with quantitative analysis. The data was collected from 60 students of English education at Universitas Negeri Padang. The instrument of this study was a questionnaire of the used of reading strategy adapted from Mokhtari & Sheorey (2002). The strategies were divided into three groups: support, problem-solving, and global. The findings indicate that the use of all three reading strategies among students is high, with an overall frequency level of 77%. Specifically, problem-solving strategies are the most frequently used at 85%, followed by global strategies at 75%, and support strategies at 70%. This suggests that students frequently utilize reading strategies, with problem-solving strategies being the most commonly used.